Komposisi Nekleotida Sekuen Gen Mitokondria 16S rRNA Ikan Bilih (Mystacoleucus padangensis Bleeker, 1852) Danau Singkarak, Solok, Sumatera Barat - Liza Oktavia; Tuty Arisuryanti (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Bilih fish (Mystacoleucus padangensis) is one of the endemic fish inhabited at West Sumatra and is exploited extensively to meet market demands due to high nutritional value. The fish is also commonly exported to Malaysia and Singapore in dried processed form. However, research on composition of mtDNA 16S nucleotide as a part of genetic characterization of bilih fish has not been examined. Genetic characterization of the fish is useful for its conservation and breeding program. Therefore, the aim of this research was to determine composition of mtDNA 16S nucleotide of bilih fish (Mystacoleucus padangensis Bleeker, 1852) collected from Singkarak Lake, Solok, West Sumatra. This research used a PCR method with 16S universal primers: 16Sar and16Sbr. The results showed that the average of mtDNA 16S nucleotide composition was T=22.63%, C=24.38%, A=31.24% and G=21.76% whereas the average of A+T and C+G were 53.86% and 46.14% respectively. The difference in the mtDNA 16S nucleotide between the two bilih fish samples was similar between T, C, and A composition (0,04%) whereas the G composition was high (0,13%). In addition, the average rate of nucleotide composition A+ T and G+ C between the two bilih fish samples was similar (0,08%). This result revealed that there was genetic variation between the two bilih fish samples examined in this study based on composition of mtDNA 16S nucleotide which is the first published data we reported.